1970
DOI: 10.1007/bf02531459
|View full text |Cite
|
Sign up to set email alerts
|

trans‐6‐Hexadecenoic acid in the Atlantic leatherbackDermochelys coriacea coriaceaL. and other marine turtles

Abstract: Depot fat from the Atlantic leatherback turtle (Dermochelys coriacea coriacea L.) was shown to contain ≈3% oftrans-6-hexadecenoic acid. Structural details were elucidated through comparative aspects of isolation techniques, NMR, IR, hydrogenation, oxidative fission, etc., and confirmed by similarity of properties with those of a sample of fatty acid of this structure isolated from the seed oil ofPicramnia sellowii. One additional leather-back turtle oil sample, and depot fat from two other marine turtles, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In a previous study cis 16: lo10 did not appear in this position in G.L.C. analyses on butanediol-succinate (2). The identity of this acid is not known at the time of writing, but cis 16 : 1 w l l is suspected.…”
Section: Monoetkzylenic Acidsmentioning
confidence: 78%
“…In a previous study cis 16: lo10 did not appear in this position in G.L.C. analyses on butanediol-succinate (2). The identity of this acid is not known at the time of writing, but cis 16 : 1 w l l is suspected.…”
Section: Monoetkzylenic Acidsmentioning
confidence: 78%
“…Thus the presence of these fatty acids in both leatherback turtles and ocean sunfish was taken as an indicator of a diet containing jellyfish (Ackman 1997). The role of jellyfish in the diet of M. mola remains unclear, however, since the study that identified trans-6-hexadecenoic acid in D. coriacea also identified it in two other turtle species: the loggerhead Caretta caretta and Kemp's Ridley Lepidochelys kempii (Hooper and Ackman 1970), both of which are omnivorous, not obligate feeders on jellyfish (Bjorndal 1997). A proposed link between these fatty acids and predation on jellyfish becomes less certain when subsequent studies also identified both fatty acids in the liver oil of the reef-dwelling Atlantic spadefish Chaetodipterus faber (Pearce and Stillway 1976) and 7-methyl-7-hexadecenoic acid as a constituent of sperm whale oil (Pascal and Ackman 1975).…”
Section: Dietmentioning
confidence: 97%
“…Trans-6-hexadecenoic acid was known to comprise 2% of the total fatty acids in the moon jellyfish Aurelia aurita (Hooper and Ackman 1972). In addition, both of these fatty acids had previously been isolated from tissues of the leatherback turtle, Dermochelys coriacea (Hooper and Ackman 1970), an animal known to be an obligate gelatinous zooplanktivore (Houghton et al 2006c). Thus the presence of these fatty acids in both leatherback turtles and ocean sunfish was taken as an indicator of a diet containing jellyfish (Ackman 1997).…”
Section: Dietmentioning
confidence: 98%
“…The giant ocean sunfish Mola mola Hooper er al. 1973), the even larger leatherback turtle Demchelys coriacea coriacea (Hooper and Ackman 1970) and the spadefish Chaetodiptents faber (Pearce and Stillway 1976) all accumulate trans-6-hexadecenoic acid from jellyfish. Green turtles Chelonia mydas are herbivores in the Caribbean (Joseph er al.…”
Section: Trans Acids I N Bacteriamentioning
confidence: 99%